RANGKAIAN LAMPU EMERGENCY UNTUK MINIATURE RUMAH ADAT BETAWI DENGAN TRANSISTOR DAN MODUL TP4056 - Hafidz Atsal; Irfan Ramadhan; Pipin Tri Hastuti; Sintia Rahayu Fatmawati (Jurnal Elektronika Listrik dan Teknologi Informasi Terapan, 2023)
The Betawi Traditional House, especially the Kebaya House, has a large terrace which is used for entertaining guests and as a place for family relaxation. In ancient times, the Betawi people made a well in front of their house and a cemetery next to the house. And, the walls of his house are made of panels that can be opened and shifted to the edges. This is intended to make the house feel more spacious. The purpose of this research is to design emergency lights that can be used when the power goes out, so that this spacious kebaya house has at least lighting. The design starts from assembling the devices connected with tenol and solder, then the design of the kebaya house and finally the application